Standardization of protocol for genomic DNA extraction and microsatellite marker (SSR, ISSR) analysis in spine gourd (Momordica dioica) (Current Horticulture, 2024)
The study evaluated reliable, easy and an efficient protocol for DNA extraction from young leaves of spine gourd which yielded highly pure with no visible discoloration concentrated genomic DNA ranged from 1202.68 to 3786.92 µg/500 mg of tissue with ratio (A260/A280) of absorbance ranging from 1.34 to 1.95. This method involved modification in original cetyl trimethyl ammonium bromide extraction without liquid nitrogen and by adding high level of β-mercaptoethanol, extracting twofold with chloroform: isoamyl alcohol (24: 1, v/v) and extending the centrifugation time which successfully removes polyphenols, chlorophyll pigments, polysaccharides and dyes. The DNA extracted by this method produced clearly scorable and reproducible definitive PCR fragments authentic exhibiting its compatibility and manifesting its affinity for SSR and ISSR markers. Therefore this method is recommended as an efficient protocol for genomic DNA extraction and microsatellite marker-based genetic analysis in spine gourd for high outp ut sample preparation for diverse PCR-based downstream applications.
Keywords: DNA extraction; Inter simple sequence repeat (ISSR); PCR amplification; Simple sequence repeat (SSR)